By Investing Renewable Energy Technologies, How Spain Could Meet Its Energy Needs In 2030 And Reduce Its Domestic Greenhouse Gas Emission - Cengiz, Mazlum (Şırnak Üniversitesi, 2019)
In this study, energy supplies of Spain, solar and geothermal energy resource potential of Spain, energy needs of Spain in 2030, 110Mtoe, based on population change, and how this energy demand can be supplied by renewable energy sources in order to achieve its target of reducing domestic greenhouse gas emissions at least 40% by 2030 were examined. Building a photovoltaic power plant that has a capacity of 2000 MW per year and a flash geothermal plant which is suitable for low temperature developments has a capacity of 683 MW per year were proposed to meet energy need of the country in 2030. The estimated cost of the photovoltaic solar power plant, and the flash geothermal plant were calculated. Furthermore, the greenhouse emission from the photovoltaic solar plant and the geothermal plant was presented and the results are compared with the greenhouse emissions from a natural gas plant. The required land area for these two renewable energy plants are evaluated, as well. Moreover, the obstacles, which are water footprint of the solar photovoltaic power plant and flash geothermal plant, monitoring and track these new technologies and required land area for these energy plants, of developing these new technologies are discussed and suggestions that could assist with overcome these obstacles are given.
Keywords: Renewable Energy; Spain; Greenhouse Gas Emission; Solar Energy; Geothermal Energy